Nanocrystalline Ni5P4: a hydrogen evolution electrocatalyst of exceptional efficiency in both alkaline and acidic media1. Issue 3 (5th March 2015) - Laursen, A. B.; Patraju, K. R.; Whitaker, M. J.; Retuerto, M.; Sarkar, T.; Yao, N.; Ramanujachary, K. V.; Greenblatt, M.; Dismukes, G. C.
<x xml:space="preserve">Abstract</x> Crystalline Ni5P4 evolves hydrogen with electrical-efficiency comparable to platinum—while being corrosion-resistant in both acid and base for >16 hours.